2002
DOI: 10.1002/ptr.841
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and morphometric analyses of acetic acid‐induced colitis in rats after treatment with enemas from Myracrodruon urundeuva Fr. All. (Aroeira do Sertão)

Abstract: The present work showed the effects of Myracrodruon urundeuva Fr. All., popularly known as 'aroeira' (AE), in the form of enemas prepared from the stem bark, on several morphologic and morphometric parameters after acetic acid-induced colitis in rats. Enemas from 5-ASA were used as standard while the vehicle, carboxymethylcellulose, was used as a control. The results of the morphological evaluation showed that on day 1 acetic acid produced significantly more necrosis in the groups treated with AE (10% and 20%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
(14 reference statements)
1
16
0
5
Order By: Relevance
“…In this sense, Rodrigues et al (2002) showed the effects of M. urundeuva, in the form of enemas prepared from the stem bark, on several morphologic and morphometric parameters after acetic acid-induced colitis in rats. Results evidenced that animals treated with M. urundeuva showed complete epithelial tissue regeneration, while in the controls chronic inflammatory exudate persisted and tissue regeneration occurred through fibrosis.…”
Section: Myracrodruon Urundeuva Allemão Anacardiaceae (Aroeira-do-sementioning
confidence: 98%
“…In this sense, Rodrigues et al (2002) showed the effects of M. urundeuva, in the form of enemas prepared from the stem bark, on several morphologic and morphometric parameters after acetic acid-induced colitis in rats. Results evidenced that animals treated with M. urundeuva showed complete epithelial tissue regeneration, while in the controls chronic inflammatory exudate persisted and tissue regeneration occurred through fibrosis.…”
Section: Myracrodruon Urundeuva Allemão Anacardiaceae (Aroeira-do-sementioning
confidence: 98%
“…Pesquisas com vistas à avaliação científica da eficácia terapêutica têm mostrado evidente efeito antiinflamatório, cicatrizante, antiulcerogênico, antihistamínico, antibradicinina e analgésico (Viana et al, 1997;Rodrigues et al, 2002). Devido ao uso intenso e predatório, a M. urundeuva foi incluída na lista oficial do IBAMA como espécie ameaçada de extinção, na categoria vulnerável (IBAMA, 1992).…”
Section: Materials E Métodounclassified
“…The leaves, seeds, twigs, and stems of the "aroeira" (Myracrodruon urundeuva), a tree that is widely present throughout Brazil, have been studied because of their antifungal, anti-adherent, and antimicrobial activities (Machado and Oliveira 2014). Among "aroeira" extract properties, described in the literature with in vivo models, the following benefits can be pointed out: healing effects (Nunes Jr. et al 2008); anti-inflammatory effects (Rodrigues et al 2002;Souza et al 2007), and antiulcerative effects (Souza et al 2007). Another extract property of "aroeira" (Machado and Oliveira 2014) is its antimicrobial effect.…”
Section: Introductionmentioning
confidence: 99%